2020
DOI: 10.21203/rs.3.rs-29970/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The combined usage of Matrine and Osthole inhibited endoplasmic reticulum apoptosis induced by PCV2

Abstract: Background: Porcine circovirus type 2 (PCV2) is an important DNA pathogen commonly in pig farms, which can cause immunosuppression and induce apoptosis. To evade clearance by the host immune system, PCV2 constantly builds up complex mechanisms or mutates genes, it is difficult to eradicate complex PCV2 infection by relying on vaccine immunity and one compound. At present, there is no literature report on the effective prevention and treatment of PCV2 infection by the combined a of two or more compounds through… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It was reported that Matrine combined with Docetaxel had a synergistic effect on prostate cancer [28] and Osthole combined with Cisplatin had synergistic effect on the Rhabdomyosarcoma TE671 Cells of sarcoma [29]. This study revealed that the replication of PCV2 in mouse liver was synergisticly inhibited by the combined use of Matrine and Osthole, which was consistent with the previous results that Matrine combined with Osthole had synergistic anti-PCV2 in vitro [13].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It was reported that Matrine combined with Docetaxel had a synergistic effect on prostate cancer [28] and Osthole combined with Cisplatin had synergistic effect on the Rhabdomyosarcoma TE671 Cells of sarcoma [29]. This study revealed that the replication of PCV2 in mouse liver was synergisticly inhibited by the combined use of Matrine and Osthole, which was consistent with the previous results that Matrine combined with Osthole had synergistic anti-PCV2 in vitro [13].…”
Section: Discussionsupporting
confidence: 91%
“…The total protein was extracted from the liver and spleen of the mice and the concentration was determined using Beyotime Biotechnology kit (Beyotime Biotechnology, Jiangsu, China). The protein samples were separated by SDS-PAGE, then transferred onto the PVDF membrane [13,32]. The membrane was blocked for 2 h with 5% skim milk and then incubated with the primary antibody at 4°C overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 3 more Smart Citations